The all new Captain Underpants extra-crunchy book o' fun 2 - Pilkey, Dav, 1966- (New York : Blue Sky Press, 2002)
Learn how to draw your favorite characters, tell cheesy jokes, and even make your own silly Captain Underpants story. Also includes a new comic-book adventure starring Captain Underpants, Super Diaper Baby, and the amazing Diaper Dog.
"RL 3"--Page 4 of cover.
"Ages 7-10"--Page 4 of cover.
Keywords: Pilkey, Dav, -- 1966- -- Characters -- Captain Underpants -- Juvenile literature; Captain Underpants -- (Fictitious character); Wit and humor, Juvenile; Games -- Juvenile literature; Puzzles -- Juvenile literature; Amusements -- Juvenile literature; Creative activities and seat work; Games; Schools -- Fiction; Heroes -- Fiction; Wit and humor; Jokes; Puzzles and games; Juvenile works; Humorous fiction; Literature